Trade secrets and innovation: Evidence from the "inevitable disclosure" doctrine - Andrea Contigiani; David H. Hsu; Iwan Barankay (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
Does heightened employer-friendly trade secrecy protection help or hinder innovation? By examining U.S. state-level legal adoption of a doctrine allowing employers to curtail inventor mobility if the employee would "inevitably disclose" trade secrets, we investigate the impact of a shifting trade secrecy regime on individual- level patenting outcomes. Using a difference-in-differences design taking un-affected U.S. inventors as the comparison group, we find strengthening employer-friendly trade secrecy adversely affects innovation. We then investigate why. We do not find empirical support for diminished idea recombination from suppressed inventor mobility as the operative mechanism. While shifting intellectual property protection away from patenting into trade secrecy has some explanatory power, our results are consistent with reduced individual-level incentives to signaling quality to the external labor market.
Keywords: 330; innovation; trade secrets; knowledge workers; labor markets; inter-firm mobility